KARAKTERISASI DAN UJI DAYA HASIL PENDAHULUAN BEBERAPA GENOTIPE MENTIMUN (Cucumis sativus L.) HIBRIDA - Firmansyah, Rico; Ema Sustia Dewi, Ni Kadek; Wibowo, Ari (Jurnal Agrivet, 2025)
Cucumber is a horticultural commodity with a wide market share and high consumer demand. This study aimed to obtain preliminary information on the yield performance of several hybrid cucumber genotypes and to identify the genotypes with the best yield potential. The experiment was conducted using a Randomized Completely Block Design (RCBD) with a single factor, namely cucumber genotype, consisting of eight treatments: five hybrid genotypes (KE-6404, KE-6405, KE-6408, KE-6412, and KE-6414) and three commercial check varieties (Hercules Plus F1, Zatavy F1, and Mercy F1). Data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% level. The results showed that the evaluated genotypes and check varieties exhibited leaf shapes classified as angular or pointed. The basic fruit skin colors observed included 5 GY 3/4, 5 GY 4/6, 7.5 GY 3/4, and 7.5 GY 4/6, with fruit bases either blunt or pointed, and no bitterness detected at the fruit base. Fruit tip shapes varied among rounded, pointed, and blunt forms. Among the tested materials, genotype KE-6414 demonstrated higher yield potential compared to the other genotypes and produced fruit number per plant, fruit weight, fruit weight per plant, and yield per hectare comparable to the commercial varieties Hercules F1 and Mercy F1.